2020
DOI: 10.3390/ijerph17072461
|View full text |Cite
|
Sign up to set email alerts
|

Biosensors in Occupational Safety and Health Management: A Narrative Review

Abstract: A sensor is a device used to gather information registered by some biological, physical or chemical change, and then convert the information into a measurable signal. The first biosensor prototype was conceived more than a century ago, in 1906, but a properly defined biosensor was only developed later in 1956. Some of them have reached the commercial stage and are routinely used in environmental and agricultural applications, and especially, in clinical laboratory and industrial analysis, mostly because it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…On the other hand, if we maximize transparency, employees may have serious concerns about sharing the information about their health statuses and health-related behaviors within the organization. This ethical issue can be especially profound if more advanced biosensors are used in future health promotion programs that automatically collect and share personal data with the gamification system [ 19 ]. In order to develop effective but also ethical gamification systems, a more dedicated study is needed to find the optimal balance between transparency and privacy, perhaps through participatory design [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, if we maximize transparency, employees may have serious concerns about sharing the information about their health statuses and health-related behaviors within the organization. This ethical issue can be especially profound if more advanced biosensors are used in future health promotion programs that automatically collect and share personal data with the gamification system [ 19 ]. In order to develop effective but also ethical gamification systems, a more dedicated study is needed to find the optimal balance between transparency and privacy, perhaps through participatory design [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, one-on-one human coaching is not scalable. With the recent advances in big data, sensor network [19] and internet of things, the fourth industrial revolution (also known as Industrial 4.0) may mitigate the limitations of traditional health promotion programs and offer a lever for a qualitative leap in the field of occupational health. A particular promising solution in this technological revolution is the use of mobile gamification systems to support individuals to self-manage their diseases and/or to adopt healthier lifestyles [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…However, employee safety training has also gained attention to equipping employees with safety skills and knowledge (Mazzetti et al, 2020) and (n = 3) papers more focused on employees safety training. The instruments used in these studies were mostly adopted, and our review also found that (n = 4) used different theories for example (Baldassarre et al, 2020;Lee, 2018;Liu et al, 2020). The findings revealed that the number of mediators and moderators have been used to improve the occupational health and safety performance in most risk hazardous organizations.…”
Section: Research Context and Methodologymentioning
confidence: 86%
“…The poor conceptualization for safety management practices and interchangeable terms compel for development of a holistic framework that encompasses different aspects of safety management practices (Autenrieth et al, 2016). Besides, in previous research studies, scholars have identified the role of safety management practices to enhance occupational health and safety performance (Almost et al, 2019;Baldassarre et al, 2020;Hanafi et al, 2018;Lee, 2018;Liu et al, 2020;Vinodkumar and Bhasi, 2010;Zimolong and Elke, 2006). However, the rate of accidents, injuries, and health and safety expenses revealed the fundamental concerns for the study designs and safety management models (Alingh et al, 2018;Amponsah-Tawaih and Adu, 2016;Aziz, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…A prototype of the SMART system was created and implemented in a pilot study in an ED waiting room. The development of this prototype provided useful considerations in the implementation of a continuous patient monitoring system, including the fact that these types of sensors must be cost-effective, accurate, have the capability to communicate data while ensuring privacy/confidentially, and could be used for early diagnosis or to facilitate experts' diagnostics that allow for protecting patients against further risks [41,[50][51][52]. In addition, physical sensor limitations, such as battery life, power source, sensor durability, easy-to-use, and carrying case impact system use implementation [51].…”
Section: Continuous Patient Monitoringmentioning
confidence: 99%